The ridiculous sublime in Don DeLillo’s White Noise and Cosmopolis - Behrooz, Niloufar; Pirnajmuddin, Hossein (Penerbit Universiti Kebangsaan Malaysia, 2016)
The sublime figures significantly in Don DeLillo’s novels. Transformed into what has been termed postmodern sublime - disposing of transcendence in favor of immanence - it is considered to be more of a hollow, confusing and overwhelming phenomenon rather than an elevating and empowering one. Moreover, the multiplicity of prior representations and the exhaustion of the possible have undermined the authenticity and power of the sublime, turning it into pseudo-sublime and mock-sublime. As such, it has moved ever closer to the realm of the ridiculous to the point where it is rather a question of co-existence and coimplication between them rather than an opposition. This can be phrased the ridiculous sublime. This paper focuses on DeLillo’s White Noise (1984) and Cosmopolis (2003) by drawing on major theorists of the sublime like Kant, Jameson, Zizek and, most notably, Lyotard, in an attempt to shed light on the modality of the merging of the sublime and the ridiculous. Our analysis shows that in DeLillo’s fiction, White Noise and Cosmopolis, the events and phenomena that transpire to convey a sense of sublimity are almost always interrupted and tarnished by an implication of the grotesque and the ridiculous. This transformation of the concept of the sublime reflects the decline of metanarratives and the exhaustion of possible experiences as the hallmarks of the postmodern era.